Combination Immunosuppressive Therapy in Primary Autoimmune Inner Ear Disease in Pregnancy - Saikrishna Ananthapadmanabhan; Joe Jabbour; David Brown; Vanaja Sivapathasingam (Case Reports in Otolaryngology)
Objective. Autoimmune inner ear disease (AIED) is a rare disorder characterized by rapidly progressive, sensorineural hearing loss that demonstrates good responsiveness to corticosteroid and immunosuppressive therapy. The pathophysiology is likely driven by chronic trafficking of immune cells into the inner ear, targeting inner ear proteins to coordinate inflammation. Suppression or modulation of the immune response can minimize cochleitis allowing for potential recovery of hearing. It is an otologic emergency requiring a multidisciplinary approach to management to commence immunosuppressive therapy. This can be achieved using steroids, immunomodulators, plasmapheresis, intravenous immunoglobulin, or biologic agents. Treatment decisions are further complicated in pregnancy and require supervision by an obstetrician and maternal-fetal medicine (MFM) specialist. Concerns include safe dosing of steroids and potential for transplacental migration of immune complexes. We provide the first comprehensive literature review on AIED and its implications in pregnancy. We frame our discussion in the context of the second reported case of primary AIED in pregnancy and the first to show excellent response to immunosuppressive therapy. Methods. We reviewed the presented case and literature on AIED. Results. A 27-year-old, pregnant, HSP-70 positive woman was diagnosed with AIED and had excellent recovery of hearing and balance following a combination of steroid treatment, augmented by oral immunomodulators, plasmapheresis, and IVIG. Conclusion. AIED is a diagnostic challenge, and treatment considerations are complex when encountered in pregnancy. Management requires multidisciplinary involvement between otolaryngologists, immunologists, and obstetricians to balance maternal and fetal health outcomes.